STRUKTUR DAN UNSUR KEBAHASAAN TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 30 PADANG - Lusita, Juvira; Emidar, Emidar (Universitas Negeri Padang, 2019)
ABSTRACT This research was conducted to describe the structure and linguistic elements of the description text of class VII students of SMP Negeri 30 Padang. This type of research is qualitative with descriptive method. The data of this study are qualitative data in the form of structure and linguistic elements of the student's description text. The data are analyzed by steps, namely (1) the researcher identifies the general elements contained in the description text, (2) analyzes the essay based on the aspects studied, namely the structure and linguistic elements of the student's description text, (3) the results of the analysis the researcher examined by triangulation informants, (4) make conclusions. Based on the results of the study, two things are summarized as follows. First, in writing the description text the seventh grade students of Padang Public Middle School 30 have used both text structures. The two text structures are identification/general description and description of parts. This is evident from the 40 description texts that have been analyzed, there are 39 complete description texts using identification/general description and part descriptions. Second, in terms of language, the seventh grade students of Padang Public Middle School 30 still have errors. This is evident from the 422 sentences analyzed, there were 281 sentences and the EBI was incorrect. Kata kunci: Struktur Teks, Unsur Kebahasaan, Teks Deskripsi